2020
DOI: 10.1016/j.electacta.2020.136984
|View full text |Cite
|
Sign up to set email alerts
|

The development of a fully integrated 3D printed electrochemical platform and its application to investigate the chemical reaction between carbon dioxide and hydrazine

Abstract: Highlights An integrated electrochemical platform was manufactured by bi-material 3D printing. It was applied to investigate the reaction between hydrazine and carbon dioxide. Experimental results were supported by finite-element method numerical simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…The resolution is much higher than the FFF 3D-printed devices, however, longer time of fabrication, the need for post-treatment and curation, and the use of toxic resins are some drawbacks that make SLA less popular than FFF. Nevertheless, one of the first works on the Bismuth film electrodeposition 3D-printed wearable device containing the electrochemical device was fixed at the body using an elastic tape for zinc determination in sweat Dias et al (2019) Images reproduced with permission from American Chemical Society (Snowden et al, 2010;Richter et al, 2019;Sempionatto et al, 2017;Katseli et al, 2021;Dias et al, 2019), Italian Association of Chemical Engineering (Ponce de Leon et al, 2014), Elsevier (Dias et al, 2016;Cardoso et al, 2018;Mendonça et al, 2019;Cardoso et al, 2019;Silva et al, 2020;Escobar et al, 2020;Sibug-Torres et al, 2021;Cardoso et al, 2020c;Ferreira et al, 2021;O'Neil et al, 2019;Baltima et al, 2021); Brazilian Chemical Society (Cardoso et al, 2020a), Royal Society of Chemistry (Elbardisy et al, 2020) and Multidisciplinary Digital Publishing Institute (Vlachou et al, 2020).…”
Section: Examples Of 3d Printer Applications In Electrochemical Devices 3d Printed Electrochemical Cells For Sensing and Other Applicatiomentioning
confidence: 99%
See 2 more Smart Citations
“…The resolution is much higher than the FFF 3D-printed devices, however, longer time of fabrication, the need for post-treatment and curation, and the use of toxic resins are some drawbacks that make SLA less popular than FFF. Nevertheless, one of the first works on the Bismuth film electrodeposition 3D-printed wearable device containing the electrochemical device was fixed at the body using an elastic tape for zinc determination in sweat Dias et al (2019) Images reproduced with permission from American Chemical Society (Snowden et al, 2010;Richter et al, 2019;Sempionatto et al, 2017;Katseli et al, 2021;Dias et al, 2019), Italian Association of Chemical Engineering (Ponce de Leon et al, 2014), Elsevier (Dias et al, 2016;Cardoso et al, 2018;Mendonça et al, 2019;Cardoso et al, 2019;Silva et al, 2020;Escobar et al, 2020;Sibug-Torres et al, 2021;Cardoso et al, 2020c;Ferreira et al, 2021;O'Neil et al, 2019;Baltima et al, 2021); Brazilian Chemical Society (Cardoso et al, 2020a), Royal Society of Chemistry (Elbardisy et al, 2020) and Multidisciplinary Digital Publishing Institute (Vlachou et al, 2020).…”
Section: Examples Of 3d Printer Applications In Electrochemical Devices 3d Printed Electrochemical Cells For Sensing and Other Applicatiomentioning
confidence: 99%
“…Another design was explored to fabricate electrochemical cells for experiments using conventional electrodes and gas inlet, such as the report by Escobar et al (2020) (Escobar et al, 2020). The authors investigated the chemical reaction between CO 2 and hydrazine using an FFF 3D printed cell (Table 2 line K: images A and B are schemes while image C presents the real image), whose design presents a configuration with a separated compartment for each electrode interconnected by a fluidic channel.…”
Section: Examples Of 3d Printer Applications In Electrochemical Devices 3d Printed Electrochemical Cells For Sensing and Other Applicatiomentioning
confidence: 99%
See 1 more Smart Citation
“…functionalities for reaction mechanistic studies, [34] spectroelectrochemical analysis, [35,36] electroanalytical sensing [37][38][39][40][41][42] or organic electrosynthesis. [43] Recent achievements in the preparation of thermoplastic composites involving conductive additives allowed FDM 3DP to be utilized to manufacture electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The seminal work of Rymansaib et al [40] demonstrated that polystyrene/graphite/carbon nanofiber composite may be used to print electrodes applicable in electroanalytical sensing. In following works the polystyrene binder was replaced by polylactic acid (PLA) while the list of utilized conductive fillers was extended to graphene, [39,41,44] carbon black, [45] carbon nanotubes [34,46] and copper. [47] Employing cyclic voltammetric analysis with electroactive probes these works demonstrated that appropriately activated 3DP electrodes have charge transfer characteristics approaching those obtained for conventional carbon and metallic electrodes.…”
Section: Introductionmentioning
confidence: 99%